Design-Led Strategy: How To Bring Design Thinking Into The Art of Strategic Management. (February 2020) - Knight, Eric; Daymond, Jarryd; Paroutis, Sotirios
Design thinking has emerged as an important way for designers to draw on rich customer insights to enhance their products and services. However, design thinking is now also beginning to influence how corporate managers bring customer data into their day-to-day strategic planning. We call this integration of design thinking into the practice of strategic management "Design-Led Strategy" and show how it complements but extends current design-thinking perspectives. Adopting a strategy-as-practice perspective, this article identifies four archetypal practices that managers can use to strategize with design-thinking content. Its findings provide insight into the practices associated with situating design thinking within organizational practice.